2020
DOI: 10.1002/cne.24896
|View full text |Cite
|
Sign up to set email alerts
|

Sensory systems in birds: What we have learned from studying sensory specialists

Abstract: "Diversity" is an apt descriptor of the research career of Jack Pettigrew as it ranged from the study of trees, to clinical conditions, to sensory neuroscience. Within sensory neuroscience, he was fascinated by the evolution of sensory systems across species. Here, we review some of his work on avian sensory specialists and research that he inspired in others. We begin with an overview of the importance of the Wulst in stereopsis and the need for further study of the Wulst in relation to binocularity across av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 157 publications
(256 reference statements)
0
11
0
Order By: Relevance
“…Birds such as crows even use elaborate head-beak movements to build and use tools (Weir et al, 2002;Bird and Emery, 2009). Such coordinated actions require acute senses (Iwaniuk and Wylie, 2020), but most of all delicate motor planning and motor execution capabilities (Davies and Green, 1994;Brecht et al, 2019). With the exception of birdsong research, a research area that resulted in detailed knowledge on the neuroanatomy and neurophysiology of song production (Elemans, 2014;Schmidt and Wild, 2014;Murphy et al, 2017;Kersten et al, 2021), and despite the solid understanding of the neuroanatomy of the avian motor system (Dubbeldam, 2000), the neurophysiological mechanisms of motor plans and actions are rarely explored in birds.…”
Section: Introductionmentioning
confidence: 99%
“…Birds such as crows even use elaborate head-beak movements to build and use tools (Weir et al, 2002;Bird and Emery, 2009). Such coordinated actions require acute senses (Iwaniuk and Wylie, 2020), but most of all delicate motor planning and motor execution capabilities (Davies and Green, 1994;Brecht et al, 2019). With the exception of birdsong research, a research area that resulted in detailed knowledge on the neuroanatomy and neurophysiology of song production (Elemans, 2014;Schmidt and Wild, 2014;Murphy et al, 2017;Kersten et al, 2021), and despite the solid understanding of the neuroanatomy of the avian motor system (Dubbeldam, 2000), the neurophysiological mechanisms of motor plans and actions are rarely explored in birds.…”
Section: Introductionmentioning
confidence: 99%
“…That dromornithids have large, forward facing eyes (see Section 4.4.2.1), robust optic nerves (see Section 3.1.2), and enlarged morphology of trigeminal (V) innervation (see Section 4.4.1), further supports our argument that dromornithids were likely diurnal taxa with a strong reliance on stereopsis and trigeminal (V) somatosensory input. These results also suggest that caution is required when deriving functional or behavioural inference from comparisons of optic lobe absolute size, without accounting for the collective morphology of somatosensory "circuits" (e.g., [150] (p. 9)), such as those of the thalamofugal, tectofugal and third visual pathways (see Section 4.4.2).…”
Section: Optic Lobementioning
confidence: 99%
“…Furthermore, stereotyped species-specific behaviour [93,148], pecking accuracy [149], and the processing of visual information such as brightness, colour, and pattern discrimination [118], have been attributed to processes within the caudolateral telencephalon. Pettigrew and Frost [130] showed that the maxillary (V 2 ) division of the trigeminal (V) nerve, which innervates the upper bill (see Section 4.4.1 above), transmits to extensive terminal fields in the region of the rostrodorsal mesopallium (e.g., [150] (Figure 3b), see also [139]). Similarly, Dubbeldam et al [99] showed that ascending maxillary (V 2 ) and mandibular (V 3 ) trigeminal (V) projections transmitted rostrodorsally, via the nucleus basalis, to mesopallial terminal fields [140].…”
Section: Cerebrummentioning
confidence: 99%
See 2 more Smart Citations